The Effect of Tax Planning and Deferred Tax Charges on Earning Management - Nabila, Dhea Hasna; Herdianty, Selly (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study wants to find out whether tax planning affects earnings management, whether deferred tax expenses affect earnings management, and whether tax planning and deferred tax expenses simultaneously affect earnings management. Through a quantitative approach, explanatory research is used. In determining the sample, the authors used purposive sampling with a population of up to 156 companies and a sample of 42 manufacturing company data listed on the Indonesia Stock Exchange during 2017-2019. The secondary data is in the form of annual financial reports of manufacturing companies obtained through the official website of the Indonesia Stock Exchange, the company's official website, and other sources. The data collection method is the method of literature study and documentation. The analysis techniques are the classical assumption test, descriptive statistical analysis, multiple linear regression analysis, analysis of the coefficient of determination, analysis of the correlation coefficient, and hypothesis testing. The results of this study show 1) partially tax planning has a significant effect on earnings management, 2) partially deferred tax expense has a significant effect on earnings management and 3) simultaneously tax planning and deferred tax expense have a significant effect on earnings management.